Changes in spirituality during hospitalization in a school-age child: A qualitative case study - Siti Masitoh; Falasifah Ani Yuniarti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Hospitalization not only affects children's physical condition but also influences their spiritual aspects. School-age children are still in the developmental stage of spirituality, so illness experiences may shape how they understand and practice spirituality. Purpose: To explore perceived changes in the spirituality of a school-age child before and during hospitalization. Method: This qualitative case study involved one 10-year-old hospitalized child and the child’s mother. Data were collected through semi-structured in-depth interviews and field notes and analyzed using thematic analysis. Results: The findings showed changes in children's spirituality during hospitalization. Before illness, spiritual activities were routine-based and dependent on parental guidance. During hospitalization, there was an increase in spiritual awareness, indicated by independent prayer and hope for recovery. Children also began to perceive illness as a test. However, physical limitations hindered the performance of religious practices, leading children to express spirituality mainly through prayer. Conclusion: Hospitalization contributes to changes in children's spirituality, particularly in increasing spiritual awareness and meaning-making of illness. Therefore, spiritual care should be integrated into holistic nursing care for pediatric patients.